THE LAST POSITION OF OLD WORLD SCREW WORM IN IRAQ - Muntasir Al-Ani; Khawla bedan Al-Jassim; Mushtaq Al-Helfi (Basrah Journal of Veterinary Research)
Fourteen years of study from September 1996 to September 2010 included all province of Iraq. This study showed behavior and outbreak of old world screw worm from first recoded in Iraq with signal to its epidemiology. Investigation show proliferation and spread of fly in areas and the ways of reach this fly to in. many cases recorded at 60c and zeroC.erradication study where occur by using new method of spraying chemical pesticides and used ivermectin as injection s/c for animals as prevention. This technique improved that no cases were recorded in all town of Iraq especially in Basra which have big problem of infestation of old world screw worm in animals at 2004-2005. Study improve that were good professional staff of veterinarian in Iraq can eradication old world screw worm without using of sterile male fly technique of chrysomya bezziana.